R&D & Financial Performance in the Fast Food Industry: Case of McDonald’s - S. Abuganiah, Saleh Abdulrahman (Digital Repository of Theses - SSBM Geneva, 2025)
This thesis seeks to investigate the impact of McDonald’s research and development (R&D) expenditure on its financial performance. The thesis focuses on revenues and net income. Despite its utility as a strategic tool, R&D’s role remains less explored in the fast food industry. The thesis will use McDonald’s financial data and employs quantitative case study methodology, applying multiple regression analysis to assess the relationship between R&D spending, revenues, and net income, SG&A expenditure included as a control variable. The findings indicate that R&D expenditure does not have a statistically significant positive effect on either revenues or net income during the study period. In fact, the results suggest a weak negative association, highlighting that short-term financial performance is largely driven by SG&A rather than R&D. This implies that R&D in McDonald’s may contribute more indirectly, such as supporting long-term operational efficiency and digital transformation. The study concludes that McDonald’s should continue to invest in R&D but align these efforts with strategic priorities such as health, sustainability and technology. At the same time McDonald’s should focus on improving the integration of innovation outcomes into marketing campaigns to enhance measurable financial returns.